'Cloud Capped Towers' Made of Sand: Dissolving Barriers to Female Authorship in Julie Taymor's Tempest. (20th January 2021) - Gilreath, Philip
Abstract: Julie Taymor's 2010 film adaptation of William Shakespeare's The Tempest raises questions about how adaptation theory and film authorship are often constructed along perceptions of gender. Despite positive reactions to Helen Mirren's performance as a re-gendered Prospera, the film was critically panned on release. Critics and reviewers criticized Taymor's film technique, accusing the director of reveling in stylistic excess and relying too heavily on intrusive digital effects that overshadowed the imagination and language of the Folio play-text. These critiques draw attention to what this article suggests is most crucial to Taymor's adaptation. This article argues that Taymor's blending of the naturalistic with the artificial represent a deliberate style that emphasizes the collaborative processes of adaptation. Taymor's intercutting of digital effects and naturalistic footage emphasize the hybrid authorship of film technique—a trait embodied in Ben Whishaw's performance as the spirit Ariel. The re-gendering of Prospera furthermore situates the film against the grain of the historically gendered and romanticized conception of the film auteur as a stable and overriding masculine genius.